Differences in financial performance and stock trading activities in public companies that receive tax incentives and those that do not receive tax incentives - Risa watti; Nurul Azizah; Djojo dihardjo (Cebong Journal, 2023)
This study analyzes the differences in Financial Performance and Trading Activities between public companies in the manufacturing sector listed on the Indonesia Stock Exchange that received PP No. 30 of 2020 tax incentives and those that do not receive PP No. 30 of 2020 tax incentives. With this facility, companies that meet certain requirements can get a reduced income tax rate of 3% of the general rate. Financial performance is proxied using ratio. Profitability, and ratio, Mark. Market. price. book. value. While stock trading activity is proxied using the frequency of stock trading. The object of research is manufacturing companies that obtain PP No. 30 of 2020 facilities and manufacturing companies that did not obtain PP No. 30 of 2020 facilities during 2020 - 2021.